2019
DOI: 10.1016/j.msec.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The fight against multidrug-resistant organisms: The role of ZnO crystalline defects

Abstract: This article reports the excellent antimicrobial response of nanoparticulate ZnO against multidrug-resistant organisms (MDROs). We demonstrate that the enhanced antimicrobial activity against MDROs depends on the crystalline defects of ZnO. Hence, this work provides insights on the ZnO-microorganism interactions, and we pose combined physico-chemical action mechanisms against resistant bacteria. Highlights-Synthesis of ZnO nanoparticles with antimicrobial response against multidrug-resistant organisms.-A high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Specifically, Figure S2d (Supplementary Materials) allows observing clearly and unequivocally the nanometric character of the obtained ZnO. A close study of a particle is shown in Figure S2e It should be noted that recently we have been evidenced an excellent antimicrobial response of the nanoparticulated ZnO against multidrug-resistant organisms (MDROs), which strongly depends on the crystalline defects of ZnO [30]. In the next section, we go a step further and will demonstrate that the high antimicrobial activity can be used for the development of an inorganic composite as a paint preservative for antifungal applications…”
Section: Initial Premises: High Antimicrobial Response Of the Nanoparmentioning
confidence: 84%
See 1 more Smart Citation
“…Specifically, Figure S2d (Supplementary Materials) allows observing clearly and unequivocally the nanometric character of the obtained ZnO. A close study of a particle is shown in Figure S2e It should be noted that recently we have been evidenced an excellent antimicrobial response of the nanoparticulated ZnO against multidrug-resistant organisms (MDROs), which strongly depends on the crystalline defects of ZnO [30]. In the next section, we go a step further and will demonstrate that the high antimicrobial activity can be used for the development of an inorganic composite as a paint preservative for antifungal applications…”
Section: Initial Premises: High Antimicrobial Response Of the Nanoparmentioning
confidence: 84%
“…The choice of modified bentonite clay with Ag cations, hereafter Clay, is due to the well-known antibacterial properties of Ag [31,32]. Even, previous studies show the good antibacterial activity of this modified clay against different types of bacteria [30,33]. Therefore, it is mandatory to complement the antibacterial activity of Ag cation with a preservative against fungi such as ZnO.…”
Section: Finding a Potential Technological Application Of The Zno/clamentioning
confidence: 99%
“…ZnO is a potential antibacterial agent due to its flexibility and broad spectrum of action against microbes [ 20 , 21 ]. Based on the electric charges stored in the Schottky barriers, it was recently revealed that nanostructured ZnO microparticles have outstanding antibacterial characteristics [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of two different semiconductors can yield an efficient charge separation, leading to a vector transmission of photogenerated electrons and holes from one semiconductor material to the other [7][8][9][10]. ZnO is a semiconductor material with a wide direct bandgap of 3.2 eV, which can absorb a small part of the solar spectrum in the UV region [11][12][13]. CuO is a nontoxic, chemically stable and naturally abundant material.…”
Section: Introductionmentioning
confidence: 99%